2017
DOI: 10.4018/ijisscm.2017010101
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Selection and Assessment by University Procurement Officers

Abstract: Supplier selection and assessment is at the core of the procurement process. This study investigates how procurement officers in Israel's universities select and assess their suppliers. The authors explore which information channels officers use to assess suppliers and find that incidental and informal information sources are the most frequently used followed by official sources. The authors examine the criteria used by officers to select suppliers and identify quality and price as significantly more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Most participants used a systematic supplier selection process as part of their supplier relationship management strategy. This is in concurrence with Bouhnik, Giat and Zarruk (2017) who in their research finding concluded that organizations should implement a robust supplier selection, evaluation and assessment strategy that ensured the development of a long-term relationship with the suppliers. Five interviewees confirmed that the use of a systematic supplier selection process assisted their organization in engaging suppliers who had a potential of establishing a long-term relationship as well as supplying quality products consistently.…”
Section: Establishing a Systematic Supplier Selection Processsupporting
confidence: 71%
“…Most participants used a systematic supplier selection process as part of their supplier relationship management strategy. This is in concurrence with Bouhnik, Giat and Zarruk (2017) who in their research finding concluded that organizations should implement a robust supplier selection, evaluation and assessment strategy that ensured the development of a long-term relationship with the suppliers. Five interviewees confirmed that the use of a systematic supplier selection process assisted their organization in engaging suppliers who had a potential of establishing a long-term relationship as well as supplying quality products consistently.…”
Section: Establishing a Systematic Supplier Selection Processsupporting
confidence: 71%
“…This has resulted towards supplier's performance becoming detrimental in organization's performance. Since the concept of procurement has made gargantuan progress as a result of technological innovation, globalization and cut-throat competitiveness, organizations have started relying on procurement and the consequences of an inefficient procurement process are detrimental to the growth and sustenance of an organization (Bouhnik, Giat, & Zarruk, 2017). The procurement function involving buying raw material, supplies and components for the organization has achieved a position of extreme prominence within supply chains due to factors such as technological changes, increased value addition in supplies and rapid blurring of geographical boundaries (Boran, Genç, Kurt, & Akay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These concepts and technologies provide significant benefits to the organizations who integrate them into their organizational culture. These benefits include lower administrative costs, shorter procurement cycle, decreased inventory, lower prices, and the introduction of the organizations into technological and business partnerships (Davila, Gupta, & Palmer, 2003) and allow suppliers to assess their suppliers according to certain criteria (Bouhnik, Giat, & Zarook, 2016). These partnerships are extremely beneficial as they increase the flow of information between the supplier and purchaser using systems such as inter-organizational information systems that form an efficient marketplace (Dai & Kauffman, 2000).…”
Section: E-procurementmentioning
confidence: 99%